ANALISIS ORANG DENGAN GANGGUAN JIWA (ODGJ) DI YAYASAN DHIRA SUMAN TRITOHA - Hanifatun Nisa; Yahdinil Firda Nadhira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to understand the understanding of people with mental disorders (ODGJ) after receiving religious guidance at the Dhira Suman Tritoha Foundation Rehabilitation Center, Serang Banten. This research was conducted with a qualitative approach and descriptive method, involving interviews with research subjects consisting of ODGJ, psychological guidance, and nurses. In addition, supporting factors such as adequate infrastructure and the support of medical personnel play an important role in the guidance process. However, there are also inhibiting factors such as the frequent recurrence of mental disorder symptoms that cause decreased motivation to participate in activities.